2017
DOI: 10.1002/14651858.cd011880.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Different insulin types and regimens for pregnant women with pre-existing diabetes

Abstract: Different insulin types and regimens for pregnant women with pre-existing diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 72 publications
1
8
0
3
Order By: Relevance
“…Our findings support those of other studies that maternal adverse emotions, a common morbidity during pregnancy, can lead to poor birth outcomes 38 . Xiaoqiang, Q et al reported that psychological trauma or tension, stimulating the sympathetic adrenomedullin system and pituitary adrenocortical system, will cause a series of physiological changes and increase the risk of teratogenesis 39 .…”
Section: Discussionsupporting
confidence: 92%
“…Our findings support those of other studies that maternal adverse emotions, a common morbidity during pregnancy, can lead to poor birth outcomes 38 . Xiaoqiang, Q et al reported that psychological trauma or tension, stimulating the sympathetic adrenomedullin system and pituitary adrenocortical system, will cause a series of physiological changes and increase the risk of teratogenesis 39 .…”
Section: Discussionsupporting
confidence: 92%
“…Insulin has been used safely in pregnancy for many years as it does not cross the placenta and the FDA has sufficient evidence to classify the risk of insulin use as “low” in pregnancy 37 . A Cochrane review reported limited evidence to support one type of insulin regimen over another 38 however there is growing evidence that insulin analogues are likely to be a safe alternative to human insulin in pregnancy 37 . Although considered safe to use in pregnancy, insulin also has significant disadvantages as it can cause maternal hypoglycaemia, increase weight gain and requires education in administration and the inconvenience of multiple injections 39 .…”
Section: Short‐ and Long‐term Impact Of Treatment Of Gdm On Fetal Devmentioning
confidence: 99%
“…Both multiple daily insulin injections and continuous subcutaneous insulin infusion are reasonable delivery strategies, and neither has been shown to be superior during pregnancy (59). A recent Cochrane systematic review was not able to recommend any specific insulin regimen over another for the treatment of diabetes in pregnancy (67). has concluded that this approach would reduce morbidity, save lives, and lower health care costs (70).…”
Section: Insulinmentioning
confidence: 99%